2008
DOI: 10.1007/s11127-008-9285-y
|View full text |Cite
|
Sign up to set email alerts
|

Do fiscal rules cause budgetary outcomes?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
2
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 20 publications
3
54
2
3
Order By: Relevance
“…Several other applications reported both fe and fevd results (e.g. Caporale et al, 2009;Mitze, 2009;Krogstrup and Wälti, 2008). In the studies we examined, the fe t-statistics were consistently smaller than those reported for fevd time-varying variablesand often much smaller -except for few cases affected by robust standard error formulae.…”
Section: Variance Formulaementioning
confidence: 58%
“…Several other applications reported both fe and fevd results (e.g. Caporale et al, 2009;Mitze, 2009;Krogstrup and Wälti, 2008). In the studies we examined, the fe t-statistics were consistently smaller than those reported for fevd time-varying variablesand often much smaller -except for few cases affected by robust standard error formulae.…”
Section: Variance Formulaementioning
confidence: 58%
“…revenues are higher than expected (i.e., in expansions), they should not be used to increase expenditure 8 . In the next sub-section I present a model that incorporates these issues.…”
Section: Page 3 Of 10mentioning
confidence: 90%
“…The increase of fiscal rules from fewer than five countries in the 1970s and 1980s to 30 countries after the 1990s [3] may partially be explained by the effectiveness of numerical fiscal rules in curtailing budget deficits in different parts of the world at different levels of government, such as, USA [4][5][6], Latin America [7] and Switzerland [8] 3 .…”
Section: Introductionmentioning
confidence: 99%
“…La rapide diffusion de ce type d'institution a permis l'émer-gence d'une littérature empirique exploitant des données multipays visant à évaluer 14. La Suisse présente également des institutions budgétaires permettant d'établir une relation causale entre règles et déficits (Krogstrup et Wälti, 2008). Dans le cas des épisodes les plus importants, on note une utilisation plus répandue des règles s'appliquant aux dépenses budgé-taires.…”
Section: Les Mesures De L'équilibre Des Finances Publiques à Court Termeunclassified